Copper(II)-Catalyzed [3+2] Annulation of Thioamides with AIBN: Facile Access to Highly Functionalized Thiazolidin-4-ones - Pali, Pragya; Yadav, Dhananjay; Shukla, Gaurav; Singh, Maya Shankar (Synthesis, 2021)
An efficient and versatile copper-catalyzed intermolecular radical [3+2] annulation of thioamides with azobisisobutyronitrile (AIBN) is described. This two-component copper(II)-catalyzed transformation is achieved in one pot via cascade formation of C–S/C–N bonds through cyclization of an in situ generated N,S-acetal intermediate derived from a β-ketothioamide. This operationally simple method allows direct access to synthetically demanding thiazolidin-4-ones in good to excellent yields containing diverse functional groups of different electronic and steric nature. The readily available reaction partners, the avoidance of expensive/toxic reagents and a gram-scale synthesis are additional attributes of this strategy. AIBN plays a dual role as a radical initiator and an unusual source of a two-carbon coupling partner. Notably, the products possess Z stereochemistry with regard to the exocyclic C=C double bond at position 2 of the thiazolidine ring.
Keywords: β-ketothioamides; AIBN; domino annulation; one-pot reaction; 1,3-thiazolidin-4-ones